PEMANFAATAN DIGITAL MARKETING BAGI USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) SENTRA MAINAN ANAK KAMPUNG DI KELURAHAN JURANGOMBO, MAGELANG - Ascharisa Mettasatya Afrilia; Prinisia Nurul Ikasari (Swadaya: Indonesian Journal of Community Empowerment, 2019)
In digital era, the use of digital marketing is so important. Utilization of digital marketing can reach consumers in a wider area so that the level of sales can be increased. But unfortunately, not all Micro and Small and Medium Enterprises (MSME) entrepreneurs understand the importance of digital marketing so that the level of sales has not been absorbed optimally. Though the potential of MSMEs is quite high. Therefore, this PKM program is carried out as a form of assistance in utilizing digital marketing for MSMEs which in the context of this service is carried out at the children's toy center of Sampangan Village, Jurangombo, Magelang. The methods used in this service are lectures, discussions and simulations. Participants get material on the basic concepts of digital marketing and photography techniques. The results obtained indicate that participants understood the basic concepts of digital marketing and photography techniques. Not only that, participants also mastered photography techniques in a simple stage. Keywords: Digital marketing, photography, social media, UMKM.